2011
DOI: 10.3892/or.2011.1384
|View full text |Cite
|
Sign up to set email alerts
|

Expression of 4F2hc (CD98) in pulmonary neuroendocrine tumors

Abstract: Abstract. 4F2hc (CD98) has been associated with tumor growth, and is highly expressed in various tumors. The aim of this study was to evaluate the clinicopathological significance of 4F2hc expression in pulmonary neuroendocrine (NE) tumors. Surgically-resected patient tumors including 16 large cell neuroendocrine carcinoma (LCNEC), 12 small cell lung cancer (SCLC), 1 atypical carcinoid (AC) and 5 typical carcinoid (TC) samples were included in this study. Tumor sections were immunohistochemically stained for 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
24
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 21 publications
3
24
0
Order By: Relevance
“…This result is consistent with studies reporting CD98 in the basolateral domain of epithelial cells (Mburu et al, 2011;Kaira et al, 2011). We also demonstrated, by FRET, direct binding of CD98 and hBD3 in cells fixed and coimmunostained with CD98 and biotin-hBD3 ( Figure 4B).…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…This result is consistent with studies reporting CD98 in the basolateral domain of epithelial cells (Mburu et al, 2011;Kaira et al, 2011). We also demonstrated, by FRET, direct binding of CD98 and hBD3 in cells fixed and coimmunostained with CD98 and biotin-hBD3 ( Figure 4B).…”
Section: Discussionsupporting
confidence: 94%
“…In addition, CD98 is highly expressed in several tumors, including lung and breast, and its overexpression is associated with a poor prognosis (Feng et al, 2006;Shames et al, 2010;Charania et al, 2013). It has been suggested that promotion of tumorigenesis is mediated by the interaction of CD98 with b 1 -integrins (Cantor and Ginsberg, 2012;Furuya et al, 2012;Kaira et al, 2011). Since downregulation of CD98 promotes cell death via apoptosis (Bulus et al, 2012), the protein has been proposed as a therapeutic target (Santiago-Gó mez et al, 2013).…”
Section: Discussionmentioning
confidence: 97%
“…Many tumors express CD98hc, and its expression correlates with poor prognosis in B cell lymphomas (Holte et al, 1987;Holte et al, 1989;Salter et al, 1989). Furthermore, nearly all studies that have examined the expression of CD98hc or CD98 light chains in solid tumors show that their expression is correlated with progressive or metastatic tumors (Esteban et al, 1990;Kaira et al, 2009a;Kaira et al, 2009b;Kaira et al, 2009c;Kaira et al, 2008;Kaira et al, 2009d;Kobayashi et al, 2008;Nawashiro et al, 2002;Nawashiro et al, 2006;Oleinik et al, 2005;Powlesland et al, 2009;Shennan et al, 2003;Xiao et al, 2005).…”
Section: Cd98 Expression In Tumorsmentioning
confidence: 99%
“…High LAT1 expression correlates with poor survival; LAT1 inhibition decreases glioma tumor cell growth (Nawashiro et al, 2006) Breast cancer cell lines LAT-1 inhibitors suppress tumor cell growth and metabolism (Shennan and Thomson, 2008;Shennan et al, 2003) (Mouse) Embryonic stem cell teratomas Genetic deletion of CD98hc blocks tumor growth (Feral et al, 2005) Blood proteins during lung cancer High soluble CD98 and two other blood proteins may be a tumor biomarker (Xiao et al, 2005) Breast tissue RNA Expression of CD98-encoding mRNAs correlates with poor prognosis (Esseghir et al, 2006) Multiple CD98hc and LAT-1 expression is higher in metastatic than primary tumor sites (Kaira et al, 2008) (Mouse) Glioma cells Overexpression of CD98 light chain LAT-1 enhances tumor growth rate in vivo (Kobayashi et al, 2008) Pulmonary tumors CD98 expression predicts poor prognosis (Kaira et al, 2009a;Kaira et al, 2009b;Kaira et al, 2009c) Renal cell cancer CD98 histological expression correlates directly with malignancy grade (Prager et al, 2009) Squamous cell carcinoma lines CD98 light chain LAT-1 inhibitor improves efficacy of cisplatin treatment (Yamauchi et al, 2009) Non-small cell lung cancer LAT-1 inhibitor BCH reduces viability of tumor cells ex vivo (Imai et al, 2010) Chicken cell line and HeLa cells Genetic disruption or inhibition of LAT-1 blocks tumor cell growth in vitro and in vivo (Ohkawa et al, 2011) allowing a cell to exert force on the ECM through integrin-driven RhoA signaling , which is a key element in the sensing of stiffness (Samuel et al, 2011). Anchorage independence (i.e.…”
Section: Cd98 Integrin Signaling Function In Cancermentioning
confidence: 99%
“…In pulmonary NETs, expression of CD98 increased from lowto high-grade tumors and high levels were associated with poor overall survival. Furthermore, its expression was associated with high levels of glucose transporter 1 (GLUT1), hypoxia-inducible factor 1-alpha (HIF1α), p-AKT, p-mTOR and p-S6K protein that are known to be implicated in NET carcinogenesis and are highly expressed in NETs (79,80). SCLC cells have been found to have high levels of soluble RE1-silencing transcription factor (sREST), which is an SCLC-specific isoform of RE1-silencing transcription factor that regulates expression of neuronal markers.…”
Section: Other Markersmentioning
confidence: 99%